High-Frequency Amplification and Sound Quality in Listeners With Normal Through Moderate Hearing Loss. - Ricketts, Todd A.; Dittberner, Andrew B.; Johnson, Earl E. (Journal of Speech, Language & Hearing Research, 2008)
Purpose: One factor that has been shown to greatly affect sound quality is audible bandwidth. Provision of gain for frequencies above 4-6 kHz has not generally been supported for groups of hearing aid wearers. The purpose of this study was to determine if preference for bandwidth extension in hearing aid processed sounds was related to the magnitude of hearing loss in individual listeners. Method: Ten participants with normal hearing and 20 participants with mild-to-moderate hearing loss completed the study. Signals were processed using hearing aid-style compression algorithms and filtered using two cutoff frequencies, 5.5 and 9 kHz, which were selected to represent bandwidths that are achievable in modern hearing aids. Round-robin paired comparisons based on the criteria of preferred sound qualify were made for 2 different monaurally presented brief sound segments, including music and a movie. Results: Results revealed that preference for either the wider or narrower bandwidth [9- or 5.5-kHz cutoff frequency, respectively) was correlated with the slope of hearing loss from 4 to 12 kHz, with steep threshold slopes associated with preference for narrower bandwidths. Conclusion: Consistent preference for wider bandwidth is present in some listeners with mild-to-moderate hearing loss. Reprinted by permission of the publisher.